Effect of Location of Zero Gauss Plane on Oxygen Concentration at Crystal Melt Interface During Growth of Magnetic Silicon Single Crystal Using Czochralski Technique. (2016) - Vegad, Mitesh; Bhatt, N.M.
Abstract: A numerical simulation approach has been adopted to investigate the effect of location of zero Gauss plane (ZGP) on oxygen concentration at crystal melt interface for growth of Silicon single crystal using Czochralski (CZ) method. ZGP location for the CUSP magnetic field has been moved above and below the melt free surface by 10% of the melt height. Crucible melt of aspect ratio 1, 0.5 and 0.25 have been taken into consideration. Oxygen concentration at crystal melt interface reduces with reduction of melt aspect ratio, irrespective of the ZGP location. Melt flow structure for low aspect ratio breaks down into two toroidal cells as compared to single cell structure for higher melt aspect ratio. Oxygen concentration at crystal melt interface varies along the radius of the crystal for high aspect ratio melt. Effect of change of location of ZGP on oxygen species incorporated into growing crystal depends on the melt aspect ratio.